Quest for participatory democracy : towards understanding the approach of Gandhi and Jayaprakash Narayan - Anand Kumar; Manish Tiwari (Rawat Publications, 2010)
Contributed articles presented at an international seminar organized by Jawaharlal Nehru University, New Delhi; with reference to India.